Liver graft hyperperfusion in the early postoperative period promotes hepatic regeneration 2 weeks after living donor liver transplantation: A prospective observational cohort study. Issue 46 (November 2016) - Byun, Sung Hye; Yang, Hae Soo; Kim, Jong Hae
Abstract : Abstract: Hepatic regeneration is essential to meet the metabolic demands of partial liver grafts following living donor liver transplantation (LDLT). Hepatic regeneration is promoted by portal hyperperfusion of partial grafts, which produces shear stress on the sinusoidal endothelium. Hepatic regeneration is difficult to assess within the first 2 weeks after LDLT as the size of liver graft could be overestimated in the presence of postsurgical graft edema. In this study, we evaluated the effects of graft hyperperfusion on the rate of hepatic regeneration 2 weeks after LDLT by measuring hepatic hemodynamic parameters. Thirty-six patients undergoing LDLT were enrolled in this study. Hepatic hemodynamic parameters including peak portal venous flow velocity (PVV) were measured using spectral Doppler ultrasonography on postoperative day 1. Subsequently, we calculated the ratio of each velocity to 100 g of the initial graft weight (GW) obtained immediately after graft retrieval on the day of LDLT. Ratios of GW to recipient weight (GRWR) and to standard liver volume (GW/SLV) were also obtained. The hepatic regeneration rate was defined as the ratio of the regenerated volume measured using computed tomographic volumetry at postoperative week 2 to the initial GW. Correlations of the hemodynamic parameters, GRWR, and GW/SLV with the hepatic regeneration rate were assessed using a linear regression analysis. The liver grafts regenerated to approximately 1.7 times their initial GW (1.7 ± 0.3 [mean ± standard deviation]). PVV/100 g of GW ( r 2 = 0.224, β1 [slope coefficient] = 2.105, P = 0.004) and velocities of the hepatic artery and vein per 100 g of GW positively correlated with the hepatic regeneration rate, whereas GRWR ( r 2 = 0.407, β1 = –81.149, P < 0.001) and GW/SLV ( r 2 = 0.541, β1 = –2.184, P < 0.001) negatively correlated with the hepatic regeneration rate. Graft hyperperfusion demonstrated by increased hepatic vascular velocities and a small-sized graft in the early postoperative period contributes to hepatic regeneration 2 weeks after LDLT.